Multifunctional RNA Processing Protein SRm160 Induces Apoptosis and Regulates Eye and Genital Development in Drosophila. - Fan, Y.J.; Gittis, A.H.; Juge, F.; Qiu, C.; Xu, Y.Z.; Rabinow, L. (Genetics, 2014)
SRm160 is an SR-like protein implicated in multiple steps of RNA processing and nucleocytoplasmic export. Although its biochemical functions have been extensively described, its genetic interactions and potential participation in signaling pathways remain largely unknown, despite the fact that it is highly phosphorylated in both mammalian cells and Drosophila. To begin elucidating the functions of the protein in signaling and its potential role in developmental processes, we characterized mutant and overexpression SRm160 phenotypes in Drosophila and their interactions with the locus encoding the LAMMER protein kinase, Doa. SRm160 mutations are recessive lethal, while its overexpression generates phenotypes including roughened eyes and highly disorganized internal eye structure, which are due at least in part to aberrantly high levels of apoptosis. SRm160 is required for normal somatic sex determination, since its alleles strongly enhance a subtle sex transformation phenotype induced by Doa kinase alleles. Moreover, modification of SRm160 by DOA kinase appears to be necessary for its activity, since Doa alleles suppress phenotypes induced by SRm160 overexpression in the eye and enhance those in genital discs. Modification of SRm160 may occur through direct interaction because DOA kinase phosphorylates it in vitro. Remarkably, SRm160 protein was concentrated in the nuclei of precellular embryos but was very rapidly excluded from nuclei or degraded coincident with cellularization. Also of interest, transcripts are restricted almost exclusively to the developing nervous system in mature embryos.